Effect of Toxic Potassium Chromate on in Vitro Growth of Artemisia tilesii Ledeb. Hairy Roots - Matvieieva, Nadiia; Duplij, Volodymyr; Luchko, Liliia; Bohdanovych, Taisa; Kuchuk, Mykola (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2025)
Chromium contamination, prevalent due to its extensive industrial application, poses a significant environmental threat. Hexavalent chromium is notably more toxic than its trivalent form. Phytoremediation, leveraging plants’ natural detoxification mechanisms like oxidative stress counteraction, synthesis of reducing compounds, and conversion of Cr(VI) to less toxic Cr(III), offers a promising remediation strategy. Consequently, exploring plant species for their phytoremediation potential is crucial for environmental sustainability. This study investigates the phytoremediation capacity of Artemisia tilesii Ledeb. hairy roots in media contaminated with Cr(VI). Hairy roots were cultured for 7 days in Murashige and Skoog medium supplemented with Cr(VI) at concentrations of 25, 50, and 100 mg/l. Key parameters assessed included root biomass, flavonoid content, reducing activity, Cr(VI) content in both roots and medium, tolerance index, and growth-corrected bioconcentration factor. Results demonstrated that at 25 mg.L⁻¹ Cr(VI), A. tilesii hairy roots exhibited a normal growth rate, with no adverse effects on flavonoid content or reducing activity. Remarkably, these roots efficiently accumulated chromium, removing nearly 90% of the Cr(VI) from the medium. However, higher Cr(VI) concentrations proved toxic, inhibiting root growth and biosynthetic activity. In conclusion, Artemisia tilesii hairy roots show significant potential for phytoremediation of Cr(VI)-contaminated environments, particularly when chromium concentrations do not exceed 25 mg.L⁻¹. This highlights its promise as a sustainable and effective tool for environmental clean-up.